An examination of the relation of scientific thought to changing notions of time, space and character in 20th century drama: Chekov, Beckett, Foreman - Wilsenach, Cobaâ€ Maryn (Department of Drama, 2015)
This study examines and investigates the relation of scientific thought to changing notions of time, space and character in twentiethâ€ century drama. The aim of the study is to illustrate the influence scientific thought had on the zeitgeist of the twentiethâ€ century and how this in turn is reflected through the drama in the treatment of the dramatic elements of time, space and character. The focus of the study rests on three case studies, each of which can be seen as a precursor to the following in a linear timeline of the development of twentiethâ€ century drama. The analysis of the three texts, namely Anton Chekhov's The Cherry Orchard, Samuel Beckett's Waiting for Go dot and Richard Foreman's Bad Boy Nietzsche, will show how the philosophical notions of the twentiethâ€ century, namely relativity, uncertainty, ambiguity, paradox, complexity and causality (which stemmed from the changing worldview offered by the theory of relativity) is reflected in the dramatists' handling of the notions of time, space and character.